Experiments with TeX and hyperactivity - Carr, L; Rahtz, S; Hall, W (TeX Users Group, 1991)
Publishers are starting to explore ways of making their traditional books available on screens, using techniques grouped together as "hypertext", and have tended to concentrate on the problems of linkage and navigation. We believe that both structured writing and traditional tjpesetting skills have an important part to play in the screen-oriented books to come, and we present the results of various experimental systems which use TeX in the process of creating a hypertext document. Problems tackled Include the use of TeX to format text being displayed on screen in variable sized windows. embedding generic hypertext navigation tools in the source and using a single source to generate both printed and hypertext versions of a document.